1993
DOI: 10.1007/bf01541767
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activities, desire, and satisfaction in males pre- and post-spinal cord injury

Abstract: Thirty-eight spinal cord injured (SCI) males (median age = 26) completed an 80-item multiple choice questionnaire (median 37 months postinjury) which assessed sexual functioning pre- and post-spinal cord injury in four areas: (i) sexual activities and preferences, (ii) sexual abilities, (iii) sexual desire, arousal, and satisfaction, and, (iv) sexual adjustment. Frequency of sexual activity decreased following SCI with a reduction in intercourse and increased interest in alternative sexual activities. Of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
78
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 5 publications
14
78
1
7
Order By: Relevance
“…Her study showed sexual function as the number-one priority for individuals with paraplegia and the number-two priority for individuals with tetraplegia. Other previous studies are congruent with these findings and continually stress the importance of sexual adjustment after SCI (19)(20)(21). Clinically, we have encountered many persons with SCI who were experiencing AD with sexual activity, and this was impacting their sexual adjustment.…”
Section: Introductionsupporting
confidence: 78%
“…Her study showed sexual function as the number-one priority for individuals with paraplegia and the number-two priority for individuals with tetraplegia. Other previous studies are congruent with these findings and continually stress the importance of sexual adjustment after SCI (19)(20)(21). Clinically, we have encountered many persons with SCI who were experiencing AD with sexual activity, and this was impacting their sexual adjustment.…”
Section: Introductionsupporting
confidence: 78%
“…Not only physical constraints, but also emotional distress as well as other psychological factors have the potential to change the perception of sexuality in the spinal cord injured [10,11]. Alexander et al reported an incidence of 74 % of relationship difficulties concerning sexual health after spinal cord injury in men [12]. In the last few years, new studies have emerged on sexual health in spinal cord injured women, eliciting the pathophysiology and complicated features of sexual dysfunction (SD) in women with spinal cord injury, and even more general in neurological disease [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, despite this impact, the sexual activity of individuals with SCI has largely been neglected as a focus of research and is one of the most unmet needs for this group of individuals. 4,5 In particular, although the sexual activity and coping strategies of people with SCI will likely be diverse across cultures because of cultural differences, 6,7 little research has been published regarding the sexuality of individuals with SCI, particularly in East Asia. In one of the few studies addressing this issue for an Asian population, a comparative investigation of the life satisfaction between long-term survivors of SCI in Sweden and Japan found that the percentage of sexually active (SA) males engaged in sexual intercourse was significantly lower in Japan than in Sweden, and also observed an absence of sexual counseling for disabled people in the former country.…”
Section: Introductionmentioning
confidence: 99%